O conflito assimétrico entre Israel e Palestina: a opressão sionista sob a ótica do direito internacional - Morgado, Gabriela Lacerda (2024)
This study aims to analyze the conflict between Israel and Palestine through the lens of International Law, focusing on Zionist oppression, violations of international norms, and the feasibility of establishing a sovereign Palestinian State. The research is justified by the global significance of the issue, heightened by recent events such as the October 7, 2023 offensive, and the UN Security Council's ongoing inability to achieve concrete solutions. The central hypothesis asserts that Israeli actions violate UN resolutions, customary norms, and international treaties, constituting war crimes and human rights violations. Methodologically, the study adopts the historical-dialectical materialist approach, employing documentary and bibliographical analysis, addressing historical milestones and contemporary aspects based on UN resolutions, international treaties, and academic studies. The findings reveal that Israeli occupation contravenes fundamental principles of International Law and that the establishment of a Palestinian State is legally and internationally supported, yet faces political and diplomatic challenges. The study concludes by underscoring the urgent need for global efforts to resolve the conflict, uphold Palestinian rights, and promote regional stability